Primary conjunctiva tuberculosis & review of literature - Aliff, I.C.; Ismail, Fazliana; Tajunisah, Iqbal; Zahari, Mimiwati; Chandran, Patricia Ann; Subrayan, Visvaraja (Malaysian Society of Parasitology and Tropical Medicine, 2018)
The causes of chronic conjunctivitis are exhaustive, infection being the commonest. Primary tuberculosis(TB) involving the conjunctiva is rare. History of chronicity, worsening symptoms with steroids and clinical signs of subconjunctiva nodules could point towards the diagnosis of primary conjunctiva tuberculosis especially in endemic countries. Clinicopathological diagnosis is imperative to confirm this diagnosis. We report a case of a young lady who presented with a non-resolving chronic conjunctivitis that was proven to be TB and responded well to anti-tuberculosis treatment.